Real-world media ethics : inside the broadcast and entertainment industries - Perebinossoff, Phillipe (Focal Press, 2008)
"Real-World Media Ethics is written in a friendly and approachable voice. It succeeds in offering an honest, frontline-aware, and realistic sense of the ethical situations faced by entertainment and journalism professionals every day - in the real world." "Other books about media ethics focus mostly on journalism; this book, however, covers not just journalistic ethics but also ethics in the landscape of mass media, including public relations, the entertainment industry, and other forms of visual communication. The author includes numerous case studies about current headlines that readers will already be familiar with, providing realistic and engaging scenarios about when, how, and why ethics count."--BOOK JACKET.